Design and Analysis of Butterfly Valve - et. al., R.Manikandan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this project is shape optimization and structural stability of the butterfly valve for metallic and nonmetallic materials butterfly valve is mostly used in the engine carburetors need to make structural stability and shape optimization plays the main role for this component, design modifications and material comparative analysis done in ANSYS Structural modules and find the optimized shape through stress, strain and deformation results